Allopurinol causing drug rash with eosinophilia and systemic symptoms syndrome: a challenging diagnosis - Hassan S; Wetz R; Zouein E (International Journal of General Medicine, 2011)
Samer Hassan, Robert Wetz, Elie ZoueinStaten Island University Hospital, New York, NY, USABackground: Drug rash with eosinophilia and systemic symptoms (DRESS) syndrome is characterized by cutaneous drug eruption, eosinophilia, and systemic symptoms. The syndrome is difficult to diagnose due to its clinical heterogeneity and long latency period(2–6 weeks).Case report: This paper describes a 73-year-old man who presented with a rash that started 1 week prior to his presentation. The rash was associated with fever, dyspnea, and cough. He was admitted for pneumonia and started on intravenous antibiotics. After 3 days, he became confused and developed multiorgan dysfunction. Work-up for possible hematologic disorders, autoimmune diseases, and pneumonia was negative. One month prior to the onset of the rash, allopurinol had been prescribed for asymptomatic hyperuricemia. The allopurinol was stopped and corticosteroids were started; 2 days later, the patient became afebrile and the dyspnea resolved. He was diagnosed with DRESS syndrome, which is associated with high mortality.Conclusion: The recent introduction of a drug followed by a rash, multiorgan dysfunction, and eosinophilia should raise the suspicion of DRESS syndrome. Early cessation of the introduced drug is key to survival. Clinicians should be aware of this potential adverse reaction when prescribing any new drug, including allopurinol.Keywords: DRESS syndrome, eosinophilia, drug reaction, allopurinol, multiorgan failure, hyperuricemia